The Presence of Aquatic Resources in Biological Fish Aggregating Devices (Bio-FADs) Tree Technology in the Waters of the Makassar Strait - Wayan Kantun; Muchlis Nawa; Indra Cahyono (Indonesian Journal of Coastal and Marine Studies, 2025)
Fishing for bottom fish has been so intensive that it is thought to have had an impact on ecosystem damage and changes in bottom fish populations. Based on this, this research was conducted to analyze the presence and composition of fish species in the Biological Fish Aggregating Devices (Bio-FADs) Tree installation area. This research was conducted in the Tanakeke waters of the Makassar Strait from August to September 2024. This research used an experimental method by installing three Bio-FADs Trees at three stations. The first station has habitat conditions without seagrass, the second station has damaged seagrass conditions, and the third station has good seagrass habitat conditions. Observations were made using underwater cameras for each station. The results of the research showed that the number of fish present at station one was 17 species with a total of 455 individuals, station 2 with 14 species totaling 293 individuals and station three with 11 species with 351 individuals. The highest presence at station one was Siganus guttatus fish at 22.86%, while at stations two and three the Pentapodus bifasciatus species were 18.77 and 18.52% respectively. Station one with a habitat without seagrass provides a higher presence of aquatic resources than the other stations.